2013
DOI: 10.1002/anie.201306146
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Tetrahedral P4 and As4 Molecules as Guests in Polymeric and Spherical Environments

Abstract: As you like it: [Ag(η2‐As4)2]+[pftb]− can be used to store yellow arsenic (As4). From it, As4 can be easily released to give concentrated, light‐stable solutions. These As4 solutions, and those of white phosphorus (P4), allowed molecular As4 and P4 to be encapsulated inside giant, spherical aggregates and polymeric matrices, enabling the first determination of their EE (E=P, As) bond lengths by diffraction methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
61
0
7

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 41 publications
3
61
0
7
Order By: Relevance
“…At the same time each fragment 1 is coordinated to five Cu atoms in an η 1 , η 1 , η 1 , η 1 , η 1 , η 5 -P 5 mode. The bond distances (Table 2) are close to those found in other pentaphosphaferrocene-based supramolecules [6][7][8][9][10][11][12][13][14][15]. The outer diameter of the supramolecules 2 and 3 is close to 23 Å.…”
Section: Structure Of the Supramoleculesupporting
confidence: 77%
See 2 more Smart Citations
“…At the same time each fragment 1 is coordinated to five Cu atoms in an η 1 , η 1 , η 1 , η 1 , η 1 , η 5 -P 5 mode. The bond distances (Table 2) are close to those found in other pentaphosphaferrocene-based supramolecules [6][7][8][9][10][11][12][13][14][15]. The outer diameter of the supramolecules 2 and 3 is close to 23 Å.…”
Section: Structure Of the Supramoleculesupporting
confidence: 77%
“…Our investigations during the last 10 years show that the reaction between pentaphosphaferrocenes, [Cp R Fe(η 5 -P 5 )] (Cp R = η 5 -C 5 Me 5 , η 5 -C 5 Me 4 Et, η 5 -C 5 (CH 2 Ph)) and copper(I) halides results in two general types of products, coordination polymers and oligomeric supramolecules [6][7][8][9][10][11][12][13][14][15]. We found that the coordination of CuX (X = Cl, Br, I) building blocks to phosphorus atoms of [Cp*Fe(η 5 -P 5 )] (1, Cp* = η 5 -C 5 Me 5 ) results in the formation of giant spheres with large inner cavities.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Here, P 4 was synthesized from red phosphorus and trapped by gas phase diffusion. Furthermore, we succeeded in the encapsulation and stabilization of intact tetrahedral E 4 molecules (E = P, As) in polymeric and spherical aggregates constructed by copper halides and [Cp*Fe(η 5 -P 5 )] (Cp* = η 5 -C 5 Me 5 ) 10 . Even if the corresponding crystals are air and light-stable, they are insoluble in common solvents and the group 15 tetrahedra are not releasable without the decomposition of the complexes.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Durch vorsichtiges Überschichten einer Lçsung von CuI in CH 3 .B ei der Bildung von 4,a ls jedoch ein anderes Solvatomorph (4a), entstehen auch braune Nadeln des früher beschriebenen 2D-Koordinationspolymers [{Cp*Fe(h 5 -P 5 )}(CuI)] n . [10] Offensichtlich verhindert die Anwesenheit von [Cp*Fe(h 5 -P 5 )] im Reaktionsgemisch die zunächst einsetzende Bildung von 3 und begünstigt die Bildung von 4.…”
unclassified